TRAIL-Receptor 4 Modulates γδ T Cell-Cytotoxicity Toward Cancer Cells - Tawfik, Doaa; Groth, Christopher; Gundlach, Jan-Paul; Peipp, Matthias; Kabelitz, Dieter; Becker, Thomas; Oberg, Hans-Heinrich; Trauzold, Anna; Wesch, Daniela (Frontiers in Immunology, 2019)
Pancreatic ductal adenocarcinoma (PDAC) is one of the deadliest cancers with a mortality rate almost equal to its incidence rate. Acquired immune evasion mechanisms, late diagnosis, highly aggressive growth and resistance to current therapeutic treatments, all contribute to its dismal prognosis. Recently, we observed that different γδ T cell subsets as well as CD8+ αβ T cells infiltrate the PDAC tissue. Interestingly, the abundance of γδ T cells was reported to have a positive prognostic impact on survival of cancer patients. Since γδ T cells utilize TRAIL for killing of tumor cells in addition to granzyme B and perforin, we investigated the role of the TRAIL-/TRAIL-R system in γδ T cell-cytotoxicity towards PDAC cells. Coculture of Colo357 cells with γδ T cells resulted in a moderate lysis of tumor cells. The lysis was independent of TRAIL as it was not inhibited by the addition of neutralizing anti-TRAIL antibodies or TRAIL-R2-Fc fusion protein. In accordance, knockdown (KD) of death receptors TRAIL-R1 or TRAIL-R2 in Colo357 cells had no effect on γδ T cell-mediated cytotoxicity. Interestingly, however, KD of a decoy receptor TRAIL-R4, which robustly enhanced TRAIL-induced apoptosis, almost completely abolished the γδ T cell-mediated lysis. This effect was associated with a reduced secretion of granzyme B by γδ T cells and enhanced PGE2 production as a result of increased expression level of synthetase cyclooxygenase (COX)-2 by TRAIL-R4-KD cells. Importantly, reduced release of granzyme B by γδ T cells cocultured with TRAIL-R4-KD Colo357 cells was partially reverted by bispecific antibody [HER2xCD3] and led in consequence to enhanced lysis of tumor cells. Likewise, inhibition of COX-1 and/or COX-2 partially enhanced γδ T cell-mediated lysis of TRAIL-R4-KD cells. The combination of bispecific antibody and COX-inhibitor completely restored the lysis of TRAIL-R4-KD cells by γδ T cells. In conclusion, we uncovered an unexpected novel role of TRAIL-R4 in PDAC cells. In contrast to its known pro-tumoral, anti-apoptotic function, TRAIL-R4 augments the anti-tumoral cytotoxic activity of γδ T cells.